2006
DOI: 10.1007/s10508-006-9046-2
|View full text |Cite
|
Sign up to set email alerts
|

Positive and Negative Cognitions of Sexual Submission: Relationship to Sexual Violence

Abstract: This study investigated gender differences in cognitions of sexual submission as well as their association with sexual violence. Participants were 292 heterosexual undergraduate students who completed a 56-item checklist assessing positive and negative sexual cognitions; they also completed measures assessing experiences of sexual abuse in childhood, experiences of sexual coercion in adulthood, and use of sexual coercion. Two 10-item sexual submission subscales were developed from the checklist. One reflected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…The target person was described as having had two previous sexual partners. This is consistent with the average number of partners reported by participants in previous studies with similar characteristics as the current sample (e.g., Renaud & Byers, ). The scenarios were identical except that the target's gender (“Jessica” vs. “Jason”), controllability of the onset of the STI (low control vs. high control), and STI type (herpes vs. chlamydia) were varied.…”
Section: Methodssupporting
confidence: 93%
“…The target person was described as having had two previous sexual partners. This is consistent with the average number of partners reported by participants in previous studies with similar characteristics as the current sample (e.g., Renaud & Byers, ). The scenarios were identical except that the target's gender (“Jessica” vs. “Jason”), controllability of the onset of the STI (low control vs. high control), and STI type (herpes vs. chlamydia) were varied.…”
Section: Methodssupporting
confidence: 93%
“…For example, some women regard their own sexual fantasies involving submission as negative (Byers, Purdon, & Clark, 1998;Moyano & Sierra, 2014), while some men who sexually fantasise about themes of dominance report them as negative (Byers et al, 1998). Renaud and Byers (2006) found that men and women who have experienced sexual coercion in adulthood report more negative sexual fantasies involving submission. Also, clinicians and researchers have noted that some female survivors of childhood sexual abuse report negatively appraised sexual fantasies involving force, humiliation, or pain, as well as inappropriate partners (Briere, 1992;Maltz, 2000;Westerlund, 1992;Wilson & Wilson, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, future research should be directed toward understanding the background and individual difference variables responsible for variations in women's responses to such perpetrators. For example, given empirical links between the fantasies of sexual submission and childhood sexual abuse (Renaud & Byers, 2006; Shulman & Horne, 2006), the latter may facilitate greater tolerance for rapists. Unrestricted sociosexual orientation, which has been linked to fantasies of dominance in women (Yost & Zurbriggen, 2006), may also predict ascribing positive characteristics such as charisma to sexually aggressive men when the line between submission and dominance is blurred (e.g., the “strong but flaccid” scenarios herein).…”
Section: Discussionmentioning
confidence: 99%